An Analysis of Long Run Determinants on Domestic Private Investment in Côte d'Ivoire - Diabate, Nahousse (European Scientific Journal, ESJ, 2016)
This study aims to model the long run determinants of domestic private investment in Côte d'Ivoire. Advanced econometric technique of Auto-Regressive Distributed Lag (ARDL) bounds testing approach is employed. Data from our study covers the period from 1970 to 2012. The results indicate that public investment, foreign direct investment, trade are the major determinants of short run and long run domestic private investment in Côte d'Ivoire while the real GDP growth rate and the interest rate are statistically insignificant. Thus, efforts should be geared to the development of necessary public investments in infrastructure such as supply constant electricity, good highways and elimination of the negative effects of external shocks engendered by the investment uncertainty and the deterioration of terms of trade.